Diffusion in glassy systems - Chaudhuri, Pinaki; Berthier, Ludovic; Sastry, Srikanth; Kob, Walter (Diffusion Fundamentals, 2009)
The transport properties of glass-forming systems have many features that are not found in normal liquids. Among them is a very strong sensitivity of the relaxation times upon a change in temperature and the presence of so-called dynamical heterogeneities. In this review we discuss these unusual properties and present the results of a simple lattice gas model that helps to understand the origin of these heterogeneities from the microscopic level. Furthermore we discuss a simple analytical model, the continuous time random walk, and show that it allows to describe some aspects of the relaxation dynamics of glass-forming systems on a semi-quantitative level.